Advance and Recession Studies in Border Irrigation - Kumar, Vinod; Tyagi, N.K. (Journal of Soil and Water Conservation, 2022)
This paper deals with advance and recession studies in border irrigation conducted at U.P.A.U., Pant Nagar. An exhaustive analysis of all the phenomenon taking place during different phases of irrigation is pre- sented. The results obtained by empirical method are compared with Fok & Bishop's (2) method. A field design of border irriga- tion system taking opportunity time a para- meter is also presented in graphical form for different slopes of broder.